Does firm size matter? Evidence on the impact of liquidity constraints on firm investment behavior in Germany - Audretsch,David B.; Elston,Julie (International Journal of Industrial Organization, 2001)
This paper examines the link between liquidity constraints and investment behavior for German firms of different sizes from 1970 to 1986. Results indicate that medium sized firms appear to be more liquidity constrained in their investment behavior than either the smallest or largest firms in the study, suggesting that the unique German infrastructure designed to assist the small firm has indeed succeeded in alleviating, to some degree, such liquidity constraints. Findings also support the hypothesis that the emerging competition and internationalism which characterized the German financial markets in the 1980s, have been improving access to capital for some groups of firms.
Keywords: Finance; OSU-Cascades